2018
DOI: 10.1123/jpah.2017-0318
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Public Parks of High and Low Socioeconomic Status in Colombia Using Observational Methods

Abstract: Low-SES parks need more green spaces, walk/bike trails, and areas for PA. All parks need new programs to increase the number of users and their PA level, considering sex, age group, and period of the week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
1
8
0
9
Order By: Relevance
“…Studies have investigated how SES and demographic factors alter the frequency of visiting greenspace of individuals and results are inconclusive [ 55 , 56 ]. We assessed the changes in frequency of visits to greenspace during the pandemic in relation to SES and demographic information of the survey participants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated how SES and demographic factors alter the frequency of visiting greenspace of individuals and results are inconclusive [ 55 , 56 ]. We assessed the changes in frequency of visits to greenspace during the pandemic in relation to SES and demographic information of the survey participants.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of physical activity are also characteristic of Pattern 4 of the Nutrition Transition and may be an important contributor to rising obesity in Costa Rica. Among women in Latin America, physical activity levels are low and may vary by SES, although the direction of the SES-physical activity association is unclear (Poggio et al, 2016;Aguilar-Farias et al, 2018;Camargo et al, 2018) and has not yet been evaluated in Costa Rican adults.…”
Section: Settingmentioning
confidence: 99%
“…They consistently showed that a higher percentage of those who meet the recommendations are males, younger students and those with higher socioeconomic status (SES). This trend is also evident in some Colombian studies conducted on children and adolescent populations [15][16][17][18]. Two of these descriptive studies reported that 26% of the participants met the recommendation for engaging in MVPA for 60 min per day [16,17].…”
Section: Introductionmentioning
confidence: 68%